RESPONSE OF SELECTED YIELD ATTRIBUTES OF COTTON (GOSSYPIUM HIRSUTUM L) TO VARIED ENVIRONMENTS AND SOWING ROW POSITIONS - K. K. Muhammad; S. M. Maaroof (مجلة الأنبار للعلوم الزراعية)
Understanding the impact of different microenvironments (sowing direction and sowing dates) and row locations on yield and yield component of Coker 310 cultivar were studied. in split plot design using randomized complete block design (RCBD) and three replications was applied at two succession growing seasons of 2021 and 2022 at Grdarasha Research station, College of Agriculture Engineering Science, Salahaddin University, Erbil-Iraq.The results showed that, there was significant differences for the two growing seasons on yield and its components for the different sowing dates (12 and 27, April), in addition, early sowing date possessed superiority over the delayed sowing date in bolls per plant, net ginning outturn lint index and seed cotton yield during both growing seasons. Meanwhile, the delayed sowing date was superior crop in seed index and seeds per boll during both growing seasons. Regarding sowing directions, data showed that the East-West orientation was superior in boll weight, seeds per boll, seed index and bolls per plant on the other hand in the N-S was superior in net ginning outturn and seed cotton yield in the first growing season. Meanwhile, the boll weight, bolls per plant, seed index, lint index, net ginning outturn and seed cotton yield were obtained when using N-S direction in the second growing season. Meanwhile, highest seed cotton yield produced from North-South direction in the two growing seasons (2842.93 Kg. ha-1 and 2210.39Kg. ha-1). Moreover, the statistical analysis observed to significant effect of row positions the highest values was obtained from lateral and central rows (1-3-5-7-9-11-12) for both seasons. These findings suggest that early sowing with a north-south row direction in Coker 310 cotton production might improve productivity